Productivity improvement in SME industry through new plant layout design by using witness software - Chua, Yee Leong (2013)
Productivity is a measure of performance in the industry, organization or factory. The project is focused on bread production line in a factory of Mama Bake Industry. The study is about improving production productivity, reducing the waiting time in production, increase the production in one day in order to achieve target in shorter time. Initially, collection data in terms of cycle times of each machine or workstations, the area require by the workstations. During the visit to the factory, observation period is about a day, the tools used to record time and measure distance, area required by each workstation, and area of the factory is done by using Smart Phone Atrix 2 with stopwatch and smart measure which have the function to measure the distance of the object to the user. After data are collected, following by using Witness software, the original plant layout model is created, then 4 other new layout model is created and simulate all of them together with the original layout, then the productivity and the efficiency of the layout is calculated and record in the result. From the study, the main problem found is the space are small, some process stuck due to not enough capacity in buffer provide, where the bottleneck occur, but removing the walls, and balanced the production line more buffer capacity can be provided, thus the process can proceed without delay and waiting. Among all new layouts being proposed and simulated in Witness Software, the one with higher improvement in productivity and plant layout efficiency will be chosen.